Metal‐Free O‐Arylation of Carboxylic Acid by Active Diaryliodonium(III) Intermediates Generated in situ from Iodosoarenes. Issue 20 (5th September 2017) - Dohi, Toshifumi; Koseki, Daichi; Sumida, Kohei; Okada, Kana; Mizuno, Serina; Kato, Asami; Morimoto, Koji; Kita, Yasuyuki
Abstract: The metal‐free arylative coupling of carboxylic acids using iodosoarenes without the use of a catalyst and base, which is applicable to even a highly‐polar molecule bearing multiple alcohol groups, is reported. The in situ preparation of the reactive diaryliodonium(III) carboxylates is the important key to this approach, and the introduction of the trimethoxybenzene auxiliary enables both the smooth salt formations and the selective aryl transfer events during the couplings. Abstract :